2005
DOI: 10.1029/2004jd005709
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of stratospheric liquid ternary solution aerosol from broadband infrared extinction measurements

Abstract: [1] Characterization of stratospheric liquid ternary solution (LTS) aerosol is studied as an inverse problem in retrieving particle volume size distribution and chemical composition of ternary droplets using the extinction coefficient over wavelengths of 3 to 12 mm. The retrieval method comprises a constrained, weighted least squares minimization procedure between measured and modeled spectra. The constraints restrict the first derivative of the particle size distribution with respect to particle size and rest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
1
1
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…The LTS in this model were represented as two sets of reference spectra that each had mostly binary components: one was a mixture of H 2 SO 4 /H 2 O that was 75% sulfuric acid by weight (upper left‐hand panel in Figure 1), and the other was a mixture of HNO 3 /H 2 O that was 40% nitric acid by weight (upper middle panel in Figure 1). An earlier paper [ Sasano et al , 2005] showed that inverse modeling that calculated the total PSD using primary retrievals of nitric and sulfuric acid yielded acceptable data for the total PSD, total volume density, and the AEC spectra for ternary droplets in which the chemical compositions varied widely. Therefore the PSD of the LTS was presented as a sum of those PSDs retrieved from sulfuric and nitric acid reference spectra.…”
Section: Methodsmentioning
confidence: 99%
“…The LTS in this model were represented as two sets of reference spectra that each had mostly binary components: one was a mixture of H 2 SO 4 /H 2 O that was 75% sulfuric acid by weight (upper left‐hand panel in Figure 1), and the other was a mixture of HNO 3 /H 2 O that was 40% nitric acid by weight (upper middle panel in Figure 1). An earlier paper [ Sasano et al , 2005] showed that inverse modeling that calculated the total PSD using primary retrievals of nitric and sulfuric acid yielded acceptable data for the total PSD, total volume density, and the AEC spectra for ternary droplets in which the chemical compositions varied widely. Therefore the PSD of the LTS was presented as a sum of those PSDs retrieved from sulfuric and nitric acid reference spectra.…”
Section: Methodsmentioning
confidence: 99%
“…To a large extent, the depletion of polar stratospheric ozone is controlled by the presence of PSCs, which at very low temperatures, can be quite extensive (von Hobe et al, 2006). Many satellite-based PSC observations, including those by POAM (Polar Ozone and Aerosol Measurement), SAGE (Stratospheric Aerosol and Gas Experiment), CLAES (Cryogenic Limb Array Etalon Spectrometer), ISAMS (Improved Stratospheric and Mesospheric Sounder), MIPAS (Michelson Interferometer for Passive Atmospheric Sounding) and ILAS (Improved Limb Atmospheric Spectrometer, Fromm et al, 2003;Hopfner et al, 2002;Lambert et al, 1996;Massie et al, 1997;Sasano et al, 2005) have provided a multi-decade record that shows that there is a good correlation between ozone depletion and PSC volume, both of which increase dramatically with decreasing stratospheric temperatures (Rex et al, 2006).…”
Section: Introductionmentioning
confidence: 99%